Reputation: 790
I was writing a C code for quick sort but something went wrong. After some debugging i finally found where my code was going wrong. When i replaced
{
a[lp]+=a[ub];
a[ub]=a[lp]-a[ub];
a[lp]=a[lp]-a[ub];
}
with
{
tmp=a[lp];
a[lp]=a[ub];
a[ub]=tmp;
}
my code started working. I am Curious to know why my initial implementation of swapping didn't work? Can anyone help me?
#include<stdio.h>
#define swap(a,b) (a)=(a)+(b);b=(a)-(b);(a)=(a)-(b);
int a[]={7,1,5,2,3};
int partition(int lb,int ub)
{
int k,hp,lp;
k=a[ub];
lp=lb-1;
for(hp=lb;hp<ub;hp++)
{
if(a[hp]<k)
{
lp++;
int tmp=a[lp];
a[lp]=a[hp];
a[hp]=tmp;
}
}
lp++;
a[lp]+=a[ub];
a[ub]=a[lp]-a[ub];
a[lp]=a[lp]-a[ub];
return lp;
}
void quicksort(int lb,int ub)
{
if(lb<ub)
{
int pos=partition(lb,ub);
quicksort(lb,pos-1);
quicksort(pos+1,ub);
}
}
int main()
{
quicksort(0,4);
int i;
for(i=0;i<5;i++)printf("%d ",a[i]);
printf("\n");
return 0;
}
Upvotes: 1
Views: 83
Reputation: 30597
You need to consider what happens when lp == ub (ie. you are being asked to swap an element with itself).
Change it to this:
if (lp != ub) {
a[lp]+=a[ub];
a[ub]=a[lp]-a[ub];
a[lp]=a[lp]-a[ub];
}
Example: http://ideone.com/AS1Dgf
Upvotes: 3